Application of old and new orthography in the Francophone and French press - Dedková, Iva (Romanica Olomucensia, 2023)
The present paper deals with the use of traditional and new French orthography in journalistic texts and is interested in finding out which orthography was more common during the period from 2014 to 2021. It is based on exploring a vast textual corpus composed of Francophone periodicals which is entitled "Timestamped JSI web corpus 2014-2021 French" and is integrated into Sketch Engine, a tool for studying how languages function. The paper aims to examine the competing graphic variants of 35 selected lexemes belonging to the grammatical category of nouns (anomalies and loanwords), first in the entire corpus, made up of Francophone periodicals, then in a sub-corpus, restricted to French periodicals, and finally in a sub-sub-corpus, made up of eleven selected French newspapers and magazines. The results of the study show not only the most frequent graphic variants in these corpora, but also a potential link between predominant spellings and other characteristics, such as the frequency of selected lexemes and the political or thematic orientation of the periodicals that are inspected. The paper concludes with the findings that some periodicals have a greater preference for new orthography than others, although old orthography remains widespread in this sector, which is not obliged to apply the new spellings. While there is no particular association between orthographic practices and the political orientation of the periodicals that are examined, there is a certain connection between orthographic practices and the thematic orientation of the publications that are analysed.
Keywords: French; old orthography; new orthography; press; frequency of occurrences